Novel biphenylene-diketopyrrolopyrrole-based A–π–D–π–A molecule: Synthesis, optical, electrochemical and electronical properties. Issue 28 (12th July 2017) - Zhang, Shanshan; Sun, Tao; Xu, Zhen; Li, Tianduo; Li, Yang; Niu, Qingfen; Liu, Haixia
Graphical abstract: Highlights: A novel A-π-D-π-A-type small moleculeDPP2 Ph2 is synthesized and characterized. DPP2 Ph2 showed narrow bandgap and broad absorption in 300–800 nm. DPP2 Ph2 displayed a typical aggregation-induced emission behavior. DPP2 Ph2 exhibited an efficient charge separation properties. DPP2 Ph2 is a prospective candidate as donor material. Abstract: A novel ethynyl-linked A–π–D–π–A structured moleculeDPP2 Ph2 composed of biphenylene and diketopyrrolopyrrole has been designed and synthesized. A detailed study was carried out on its optical, electrochemical, electronical, and the photoinduced charge-separation properties by using UV–Vis and fluorescence spectroscopy, cyclic voltammetry, DFT calculations and fluorescence quenching experiment. The optical results display thatDPP2 Ph2 exhibits strong and broad absorption band covering the whole visible region and has a typical fluorescence of aggregation-caused quenching (ACQ) feature. From the data in electrochemistry and fluorescence quenching experiment, theDPP2 Ph2 molecule reveals lower HOMO energy level and proper LUMO energy level to obtain efficient charge separation. These results demonstrated thatDPP2 Ph2 might be a promising donor material for organic solar cells.